Absence of CX3CR1 impairs the internalization of Tau by microglia - Bolós, Marta; Llorens-Martín, María; Perea, Juan Ramón; Jurado-Arjona, Jerónimo; Rábano, Alberto; Hernández, Félix; Avila, Jesús (Molecular neurodegeneration, 2017)
Extracellular Tau is toxic for neighboring cells, and it contributes to the progression of AD. The CX3CL1/CX3CR1 axis is an important neuron/microglia communication mechanism. We studied Tau clearance by microglia both in vitro (microglia primary cultures treated with Cy5-Tau, affinity chromatography to study the binding of Tau to CX3CR1, and Tau-CX3CL1 competition assays) and in vivo (stereotaxic injection of Cy5-Tau into WT and CX3CR1 mice). The expression of CX3CR1, CX3CL1 and the microglial phagocytic phenotype were studied in brain tissue samples from AD patients. Tau binding to CX3CR1 triggers the internalization of the former by microglia, whereas S396 Tau phosphorylation decreases the binding affinity of this protein to CX3CR1. Of note, the progressive increase in the levels of phosho-Tau occurred in parallel with an increase in CX3CR1. In addition, our studies suggest that the phagocytic capacity of microglia in brain tissue samples from AD patients is decreased. Furthermore, the CX3CR1/CX3CL1 axis may be impaired in late stages of the disease. Our data suggest that the CX3CR1/CX3CL1 axis plays a key role in the phagocytosis of Tau by microglia in vitro and in vivo and that it is affected as AD progresses. Taken together, our results reveal CX3CR1 as a novel target for the clearance of extracellular Tau.